2013
DOI: 10.5194/nhess-13-3235-2013
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variability in extreme precipitation indices over Maghreb countries

Abstract: Abstract. Maghreb countries are highly vulnerable to extreme hydrological events, such as floods and droughts, driven by the strong variability of precipitation. While several studies have analyzed the presence of trends in precipitation records for the Euro-Mediterranean basin, this study provides a regional assessment of trends on its southernmost shores. A database of 22 stations located in Algeria, Morocco and Tunisia with between 33 and 59 yr of daily precipitation records is considered. The change points… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(67 citation statements)
references
References 64 publications
2
59
0
6
Order By: Relevance
“…Tramblay et al (2013) showed that the precipitation amounts and the number of dry days over the Maghreb were significantly correlated with the MO and NAO patterns. MO and NAO showed positive trends from the 1970s onwards which could explain the trend towards decreasing frontal conditions over the Mediterranean basin and thus increasing droughts.…”
Section: Achite and S Ouillon: Recent Changes In Climate Hydrolomentioning
confidence: 97%
“…Tramblay et al (2013) showed that the precipitation amounts and the number of dry days over the Maghreb were significantly correlated with the MO and NAO patterns. MO and NAO showed positive trends from the 1970s onwards which could explain the trend towards decreasing frontal conditions over the Mediterranean basin and thus increasing droughts.…”
Section: Achite and S Ouillon: Recent Changes In Climate Hydrolomentioning
confidence: 97%
“…Cette méthode a été déjà utilisée par plusieurs auteurs (Maheras et al, 2008;Sahani et al, 2012;Ozer et al, 2007;Lupikasza, 2008;Martinez et al, 2007). Le test de Mann-Kendall permet de déceler l'existence d'une tendance globale au sein d'une série de données temporelles et a déjà été utilisé pour la détection de tendance dans les séries pluviométriques et tester leur significativité (Vannitsem et al, 1991;Norrant et Douguédroit, 2004;Maheras et al, 2008;Chaouche et al, 2010;Tramblay et al, 2013;Driouch et al, 2010).…”
Section: Zone D'étude Et Base De Donnéesunclassified
“…Les stations de Sidi Medjahed et Kenenda sont seules à montrer une baisse significative de P90 de 1,7 jour par décennie. Ces résultats coïncident avec ceux trouvés par Tramblay et al (2013) au Maghreb et d'autres auteurs en Méditerranée (Kioutsioukis et al, 2010;Norrant et Douguédroit, 2006;Brunetti et al, 2001). L'indice de l'intensité journalière (SDII) montre une tendance générale à la baisse plutôt significative aux stations de Mehdia, Derrag, Zoubiria et Sidi Medjahed qui varie entre 0,4 et 0,7 mm jr −1 par décennie.…”
Section: Analyse Des Tendances Des Indices De Pluies Journalièresunclassified
“…At the global scale, the Mediterranean region is possibly one of the most vulnerable regions to climate change because of the combination of drying and warming (Rosenzweig et al 2007; Giorgi and Lionello 2008). Analyses of the past 50 years of precipitation records in the rainy season have revealed decreasing trends in most Mediterranean regions, the exception being the northeastern Africa and the western Iberian Peninsula (Feidas et al 2007;Philandras et al 2011;Tramblay et al 2013). Projections by global and regional climate model simulations show that the decrease of winter precipitation in the European part of the Mediterranean is likely to continue during the twenty-first century (Giorgi and Lionello 2008;Hertig et al 2013).…”
Section: Introductionmentioning
confidence: 97%